Ion channels and calcium signaling in the microcirculation - Jackson, William F. (William Francis) (Current topics in membranes, 2020)
"Ion Channels and Calcium Signaling in the Microcirculation, Volume 85, the latest release in the Current Topics in Membranes series, highlights the latest advances in the expression and function of ion channels and calcium signaling in vascular smooth muscle and endothelial cells in resistance arteries, arterioles and capillaries, critical components of microcirculation, the business end of the cardiovascular system. Leading experts have contributed chapters, including Smooth muscle ion channels and calcium signaling in the regulation of striated muscle arteriolar tone; Endothelial KIR channels as a key component of shear stress-induced mechanotransduction; Endothelial TRPV4 channels and vasodilator reactivity, and much more."--Publisher's web page (viewed May 11, 2020)